2015
DOI: 10.1097/nna.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Lean Manufacturing Improves Emergency Department Throughput and Patient Satisfaction

Abstract: A multidisciplinary team led by nursing leadership and physicians developed a plan to meet increasing demand and improve the patient experience in the ED without expanding the department's current resources. The approach included Lean tools and engaged frontline staff and physicians. Applying Lean management principles resulted in quicker service, improved patient satisfaction, increased capacity, and reduced resource utilization. Incorporating continuous daily management is necessary for sustainment of contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 2 publications
1
51
0
2
Order By: Relevance
“…Few studies seemed to use well-known satisfaction assessment surveys. 81,82,89,104,107 Meanwhile, 3 studies reported either a pre-assessment or postassessment. 25,101,103 Finally, staff satisfaction/experience after LH interventions was only evaluated in 2 studies, with both reporting better results 87,101 (see Appendix 3 in Supplemental Materials, available at https://doi.org/10.1016/j.jval.2019.11.002).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies seemed to use well-known satisfaction assessment surveys. 81,82,89,104,107 Meanwhile, 3 studies reported either a pre-assessment or postassessment. 25,101,103 Finally, staff satisfaction/experience after LH interventions was only evaluated in 2 studies, with both reporting better results 87,101 (see Appendix 3 in Supplemental Materials, available at https://doi.org/10.1016/j.jval.2019.11.002).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, some EDs have shown that these core issues can be productively addressed in ways that improve both patient care and patient satisfaction. For instance, EDs have improved satisfaction by proactively communicating with patients about wait time,7 incorporating Lean manufacturing principles,8 and working with hospital leadership to reduce boarding 9…”
mentioning
confidence: 99%
“…9 Decreased length of stay, decreased waiting time to be seen, decreased throughput time, reduced adverse events, and improved patient satisfaction are among the commonly described improved care processes and patient care outcome eforts. 5,9,10,[17][18][19][20][21][22] Reduced throughput from the initial visit to treatment plan was described as a primary objective in our project. Our reduction-35 to eight business days, a 72% reduction-is in line with reports of other Lean interventions.…”
Section: Discussionmentioning
confidence: 99%